Stachys byzantina C. Koch кўкаламзорлаштиришДА истиқболли ИНТРОДУЦЕНТ ўсимлик - Ешмуратов, Р.А.; Садыков, Д.С. (SCIENCE and SOCIETY, 2020)
The article describes how to speed up the landscaping of cities and villages in the South Aral Sea region, while it is recommended to use a new decorative perspective promising introducing species Stachys byzantina C. Koch that belongs to the Lamiaceae family of the genus Stachys. Methods of study and biological properties of the plant are also described.